Evaluation of platelet function using PFA-100® in patients treated with Acetylsalicylic acid and qualified for Trauma and Orthopedic surgery procedures. (2nd October 2016) - Kurak, J.; Zając, P.; Czyżewski, D.; Kucharski, R.; Grzanka, R.; Kasperska-Zajac, A.; Koczy, B.
Abstract: The phenomenon of high on-acetylsalicylic acid (ASA) treatment platelet (PLT) reactivity – HATPR – and its clinical implications have not been fully understood. Little data is available on assessing PLT activity based on the severity of intra- and postoperative bleeding in a population of orthopedic patients with normal closure time (CT) measured by a PLT function analyzer PFA-100®, despite being given long-term ASA therapy. The aim is to assess PLT function using PFA-100® in patients with ASA therapy and qualified for trauma and orthopedic surgery procedures. The retrospective analysis covered 384 patients whose PLT reactivity was assessed using PFA-100®. Out of those, 198 had been taking ASA with a 75 mg dose until hospital admission. In addition, a group of 70 patients with a proximal femoral fracture surgically treated using the dynamic hip screw (DHS) was selected, in whom severity of bleeding was assessed by HIP ASA (+). The reference group comprised 52 patients (without ASA therapy) who were operated on due to the same indications. Normal CT was found in 37% of ASA-receiving patients. Patients with normal CT, despite ASA therapy, exhibited significantly more intense bleeding after DHS surgery. A similar number of patients required red blood cells (RBCs) transfusion in HIP ASA (+) and HIP ASA (-). Increased risk of complications in HIP ASA (+) group was not found. Conclusions: Normal PLT function assessed using PFA-100® is a common phenomenon in patients with long-term ASA treatment and who are qualified for trauma and orthopedic surgery procedures. In many cases, it seems that inadequate response to ASA is only a laboratory phenomenon.